Materials science and technology : a comprehensive treatment.Volume 16, Processing of semiconductors / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Kenneth A. Jackson - Jackson, Kenneth A.
Vol. 16 Processing of semiconductors in 1996